Transverse function control of a motorboat. (March 2016) - Hamel, Tarek; Samson, Claude
Abstract: The Transverse Function (TF) control approach is applied to the control of a generic motorboat endowed with a surge force along the stern–bow direction and a torque actuation to modify the boat's orientation. With respect to more conventional methods this approach allows for uniform practical stabilization of any smooth reference pose (i.e. position+orientation) trajectory. This includes fixed-poses in the absence of a sea-current, whose asymptotic stabilization cannot be achieved by classical feedback controllers, and non-feasible pose trajectories, i.e. trajectories that are not solutions to the system's motion equations and thus cannot be stabilized asymptotically.